Analysis of Employee Work Productivity at PT Ling Yun Indonesian Automotive Industry Technology Bekasi - Sukmayadi Sukmayadi (CV. Ulil Albab Corp, 2025)
This study aims to analyze the work productivity of employees at PT. Ling Yun Indonesian Automotive Industry Technology Bekasi. The research method used is a qualitative descriptive with data collection techniques through observation, interviews, and documentation. Data analysis uses 1 the Miles and Huberman model consisting of data reduction, data presentation, and conclusion drawing. The results showed that the work productivity of employees at PT. Ling Yun Indonesian Automotive Industry Technology Bekasi is generally quite good, but there are still several aspects that need to be improved. The skills and professionalism of employees are already in accordance with the Standard Operating Procedures (SOP), but discipline in completing production targets still needs to be improved. The work spirit and work ethic of employees are good, but self-development through routine training is still less than optimal. The quality of employee work is good with fairly high creativity. The company has been trying to maximize human resources by creating a conducive work environment and providing supporting facilities. The recommendations given include improving employee discipline, providing routine training, courses, and industrial visits for employee development, as well as maintaining and improving the already good quality of work. This study is expected to provide input for the company in an effort to improve employee work productivity.